Functional accessory limb arising from the buttock: a case report - Mohammad Mahdi Ebrahiminasab; Taghi Baghdadi; Pouya Tabatabaei Irani; Soroush Baghdadi (BMC Pediatrics)
Abstract Background Polymelia, or accessory limb, is a rare congenital abnormality with unknown etiology. Here we report the case of an infant with an accessory limb, review the diagnostic and therapeutic consideration of such cases, and highlight the potential challenges in management of an accessory limb. Case presentation We report the case of a 2-month-old male with an accessory limb arising from the left buttock. The limb was sensate and mobile joints. Our diagnostic workup did not reveal associated spinal dysraphism, but a left dislocated hip was found. The limb was surgically removed, and the hip dislocation was eventually treated with open reduction, with excellent results. Conclusion This study reports a rare case of accessory limb and reviews the important considerations in the management of this condition. Clinical trial number Not applicable.